Enhanced Antenna Design for Rectenna Application in the 2.45 GHz ISM Band - Sharif Ahmed; Zahriladha Zakaria; Mohd Nor Husain; Azahari Salleh; Ammar Alhegazi (Universitas Ahmad Dahlan, 2016)
In this paper a two layers microstrip antenna design at 2.45 GHz ISM band with Harmonic rejection filter embedded on the ground plane is presented. The two roger substrates with relative permittivity of 2.2 are separated by an air gap which enhances the antenna gain. The design is simulated using Computer Simulation Technology (CST) Studio Suite 2015. Different aperture couplings slots such as rectangular and triangular aperture coupling slots are studied and compared. It is found that the antenna with triangular aperture coupling slot enhances the antenna performance by suppressing 2nd and 3rd harmonics at 5 GHz and 8 GHz, respectively, increasing the antenna gain and providing a better circular polarization behavior. The simulated antenna design achieves a gain of 9 dB, return loss of -23.6dB, axial ratio of 1.27dB and axial-ratio bandwidth of 40.8% (2 3 GHz). The proposed antenna shows an enhancement in the antenna performance which makes it a suitable candidate for rectifying antenna or rectenna application as it can increase the total conversion efficiency resulting in a high output DC voltage used to power low power electronic and electrical devices such as wireless sensor.